2016
DOI: 10.1159/000446301
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathophysiology of Gastritis between East and West? An Asian Perspective

Abstract: among all prospected risk factors for the incidence of gastric cancer and the rate of development of gastritis. While eating habits, such as salty foods, vegetables and fruits, might influence the progression of gastritis, such factors might be responsible for the geographic heterogeneity of gastritis. Key Message: East Asian CagA-positive H. pylori is the strongest risk factor for gastric carcinogenesis and the development of gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Primer sequence (5′ to 3′) Size of PCR products (bp) References 16S rRNA-forward GCGCAATCAGCGTCAGGTAATG 502 Mona et al (2015) 16S rRNA -Reverse GCTAAGAGAGCAGCCTATGTCC CagA-Forward TTGACCAACAACCACAAACCGAAG 183 Smith et al (2002) CagA-Reverse CTTCCCTTAATTGCGAGATTCC adenocarcinoma which occurs most commonly in East Asian countries than western countries (Higashi et al, 2002;Suzuki and Mori, 2016). Since the discovery of H. pylori by Marshall and Warren (1984), it has been confirmed that H. pylori infection results in chronic active gastritis and can lead to gastric ulcer, duodenal ulcer and gastric cancer (Malfertheiner et al, 2007;Yamaoka, 2010).…”
Section: Region Amplifiedmentioning
confidence: 99%
“…Primer sequence (5′ to 3′) Size of PCR products (bp) References 16S rRNA-forward GCGCAATCAGCGTCAGGTAATG 502 Mona et al (2015) 16S rRNA -Reverse GCTAAGAGAGCAGCCTATGTCC CagA-Forward TTGACCAACAACCACAAACCGAAG 183 Smith et al (2002) CagA-Reverse CTTCCCTTAATTGCGAGATTCC adenocarcinoma which occurs most commonly in East Asian countries than western countries (Higashi et al, 2002;Suzuki and Mori, 2016). Since the discovery of H. pylori by Marshall and Warren (1984), it has been confirmed that H. pylori infection results in chronic active gastritis and can lead to gastric ulcer, duodenal ulcer and gastric cancer (Malfertheiner et al, 2007;Yamaoka, 2010).…”
Section: Region Amplifiedmentioning
confidence: 99%
“…Since 2013, H. pylori eradication therapy was approved for all cases of H. pylori gastritis by the national health insurance scheme in Japan, before other countries. From the global scale, a higher incidence of gastric cancer is found in Asia than in Europe and North America [ 5 , 6 ]. In managing effective H. pylori suppression, prevalence of H. pylori infection and incidence of resistance to antimicrobial agents in each region are important factors.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Seropositive patients for H pylori and CagA have 5.8-fold higher risk of developing GC compared to non-infected individuals, whereas patients with cagA-negative strains have 2.2-fold higher risk. 28,29 Seropositive patients for H pylori and CagA have 5.8-fold higher risk of developing GC compared to non-infected individuals, whereas patients with cagA-negative strains have 2.2-fold higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of GC is higher in Asia than in Europe and Northern America due to higher prevalence of more virulent H pylori isolates in those regions. 28,29 Seropositive patients for H pylori and CagA have 5.8-fold higher risk of developing GC compared to non-infected individuals, whereas patients with cagA-negative strains have 2.2-fold higher risk. 6 We found a significant association between cagA-positive strains and severity of the disease: 35.3% vs 81.8% in the mild-and severe-disease group, respectively.…”
Section: Discussionmentioning
confidence: 99%